Knowledge, awareness, practice patterns and attitude towards family planning methods in a tertiary centre of North India - Lata, Gagan; Gupta, Liza; Walia, Moneet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Family planning is adopted voluntarily according to the knowledge, awareness and attitude of the individuals and couples. This study aims to assess the level of awareness, knowledge, practice patterns and attitude about family planning methods in a particular area. Methods: A cross sectional descriptive study was done for 1000 married women and data was obtained by means of a questionnaire. Results: Most common encountered age group was 21-34 years (69%) in our study. Most of the women were residing in rural areas (81%) as compared to 19% in urban areas. In our study, total of 630 women (63%) were aware of family planning methods. Most of them were aware of condoms (56%), OCPs (50%), IUD (43%) and sterilization (43%). They had least information about natural methods (37%) and injectables (12%). Source of knowledge was TV and internet in 30%, friends, family and husband in 40 % and health centre and health professionals in 30% females. Majority were using condom (68%). Others were using OCPs (16%), IUD (5%) and sterilisation (2%). After counselling 55% of women agreed to use contraception and 31% were not sure whether they would use or not. Conclusions: Awareness and usage of contraceptives was low in the present study. So, there is need to educate and motivate the couples for using family planning methods.